The millipede family Niponiosomatidae new to the fauna of Taiwan, with descriptions of a new genus and two new species (Diplopoda, Chordeumatida) - Mikhaljova, Elena V.; Golovatch, Sergei I.; Chang, Hsueh-Wen (Zootaxa, 2011)
A new genus and two new species of the millipede order Chordeumatida, family Niponiosomatidae, are described from Taiwan: Taiwaneuma gen. nov., Taiwaneuma crinitum sp. nov. (the type species) and Taiwaneuma ramuligerum sp. nov. The family Niponiosomatidae is new to the fauna of Taiwan. The distributions of both new species are mapped.